“One Belt and One Road” vs. the Community of Human Destiny: Creating More Economic and Business Opportunities to the World - Liu, Hongfei; Zhang, Xinghua; Feng, Xunbo (Journal of Knowledge Management Practice, 2024)
Since being proposed by Chinese President Xi Jinping in 2013, the "One Belt and One Road (OBOR)" major initiative has been highly regarded by the international community, has responded positively to the relevant countries, and has become a Chinese national strategy. The vision and action documents for constructing "One Belt and One Road" have been formulated and written into relevant resolutions and documents of the UN Security Council. The "One Belt and One Road" initiative has actively responded to and participated worldwide in recent years. Noteworthy progress has been made in transforming the concept of "One Belt and One Road" from the vision to the real action. Compared with several significant plans in the history of world economic development, pushing forward the construction of "One Belt and One Road" has its characteristics and uniqueness. The goal of promoting the "One Belt and One Road" construction is to open wider to the outside world through promoting and further deepening reform, to achieve mutual benefit and win-win cooperation with other developed and developing countries, and to build a community of human destiny.
Keywords: knowledge management; One belt and one road (OBOR); world economy; deepening reform; cooperation and win-win; destiny community